Recycled- bottle arch as a prototype to practice sustainability through PBL / Masoume Taraz ... [et al.] - Taraz, Masoume; Haghi, Fatemeh; Mansouri, Zahra; Ghasempourabadi, Mohammad Hossein (Universiti Teknologi MARA, Perak, 2020)
This paper is a brief description of attempts of high school students during their experience to gain knowledge about environmental sustainability through an architectural project in Iran. Students are concerned with the waste materials produced by households and tried to draw the other students' attention to this issue with their project. Waste milk bottles were used as the primary material of their final project. The result of the project is a 150-centimeter-high and 160-centimeter-span arch, which had been constructed with the use of used milk bottles.